Microwave-Assisted Hydrodistillation of Essential Oil from Thymus vulgaris L. - Aberoom, P.; Porgham-Daryasari1, A.; Saber-Tehrani1, M.; Soleimani2, M. (Asian Journal of Chemistry, 2011)
Microwave-assisted hydrodistillation was used to isolate an essential oil from the aerial parts of Thymus vulgaris L. and the results compared with those obtained by conventional hydrodistillation.The essential oils extracted by microwave-assisted hydrodistillation for 20 min were similar to those obtained by hydrodistillation for 3.5 h. The microwave-assisted hydrodistillation method yields an essential oil with higher amounts of more valuable oxygenated compounds and allows substantial savings of costs, in terms of time, energy and plant material.